Answer:
y= (h(6)-h(4))/2x +C
Where C=-2*h(6)+3*h(4)
Explanation:
The secant line is the line that meets a function (in this case h(x) ) in two points, so we have to apply the ecuation of a straigt line that meets two points:
y-y1 = (y2-y1)/(x2-x1) * (x-x1)
In this case X1=4 , x2=6, y1 = h(4) and y2= h(6)
So
y-h(4)= 1/2 (h(6)-h(4)) * (x-4)
y-h(4)= 1/2 (h(6)-h(4)) x- 2 *(h(6)-h(4))
y-h(4)= 1/2 (h(6)-h(4)) x- 2 (h(6) + 2h(4))
y= 1/2 (h(6)-h(4)) x- 2 h(6) + 2h(4) + h(4)
y= 1/2 (h(6)-h(4)) x- 2 h(6) + 3h(4)
Good Luck!
*****************************************************************************
Dont forget to rate my answer if it was helpful!